Brand Marketing of Regional Products – A Potential Strategic Management Tool in Regional Development - Butoracová Šindleryová, Ivana; Hoghová, Kristína (Communication Today, 2020)
The study is based on a theory of the regional development and building of competitiveness of regions, as well as the regional labelling of products through using instruments of strategic management for the targeted direction of local marketing. Creating regional identity in the 21st century must be reﬂected in the public sector. The objective of the research was to deﬁne the inﬂuence of regional product brand existence on the efﬁcient development of territorial marketing in the analysed regions under the conditions typical for the Slovak Republic. Based on a scientiﬁc evaluation of theoretically deﬁned key terms (“region”, “regional labelling”, “regional product” or “territorial marketing”), the authors have proceeded to analyse individual brands of regional products in selected territorial units of the Slovak Republic – Kopanice; Záhorie; Hont; Ponitrie; Podpoľanie; Gemer-Malohont; Malodunajsko-Galantsko; Karsticum; Novohrad; Nitrava; and Pohronie. Within the analysis, they have conducted an empirical (quantitative) research in a form of questionnaires distributed to a target group of respondents that were deﬁned as the coordinators of regional labelling of products and services for the analysed regions; these are dominantly local action groups and civic associations operating in the given territory. The aim of the authors’ study was to identify the character of the inﬂuence that the existence of regional brands of products has on an efﬁcient increase in the promotion and awareness of the analysed regions with an objective to outline the possibilities of using the theory of regional product labelling under the conditions of the Slovak Republic within the context of territorial marketing development.